2015
DOI: 10.5765/jkacap.2015.26.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Adolescents’ Mental Health between Multicultural Family and Monocultural Family in Korea

Abstract: Objectives:With the observation of factors influencing depression, self-reported happiness, self-reported stress and suicidal attempt, this study compared and evaluated the mental health of adolescents from multicultural families and monocultural families in Korea. Methods:This study compared the characteristics of adolescents from multicultural and monocultural families based on the analysis of data of The Tenth Korea Youth Risk Behavior Web-based Survey and analyzed the factors influencing adolescent depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…For more lethal symptoms, such as history of suicide attempts and hospitalization after a suicide attempt, the risk is two to three times higher among MY than among nativeborn adolescents, although a similar result was not obtained for suicidal ideations/plans [10,12,19]. This suggests that despite the lack of difference in the prevalence of suicidal ideations/plans between MY and NKRY, MY are more likely to attempt suicide, which warrants special attention.…”
Section: Mental Health Among Multiethnic Youthsmentioning
confidence: 87%
See 3 more Smart Citations
“…For more lethal symptoms, such as history of suicide attempts and hospitalization after a suicide attempt, the risk is two to three times higher among MY than among nativeborn adolescents, although a similar result was not obtained for suicidal ideations/plans [10,12,19]. This suggests that despite the lack of difference in the prevalence of suicidal ideations/plans between MY and NKRY, MY are more likely to attempt suicide, which warrants special attention.…”
Section: Mental Health Among Multiethnic Youthsmentioning
confidence: 87%
“…They feel excluded or are dissatisfied with their peer group compared to their native-born peers [22]. Furthermore, studies that used data on Korean youth showed that MY were three to five times more likely to report being victims of school violence [10,12,23], and specifically those with foreign-born mothers were 4.1 times, and those with foreign-born fathers were 17.4 times at a higher risk of victimization respectively [75]. Given the critical role of peer relationships in the psychological adjustment of youth later in life [76,77] and the adverse effect of peer bullying on future psychopathology [78], interventions to enhance school connectedness and peer relationships are necessary for healthy MY adjustment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were 206 AMFs currently living in South Korea, who were (i) selected across eight cities from 16 regular and three multicultural schools, which are established for children of multicultural families, (ii) aged 13–18 years, and (iii) eligible as per the definition of Korea's Multicultural Families Support Act in 2011 (children of families comprising either foreigners who have South Korean citizenship or marriage immigrants). We excluded (i) refugees, (ii) AMFs with severe physical disabilities or mental health issues, and (iii) North Korean defectors as previous studies suggest that they tend to experience post-traumatic stress disorder from the process of entering South Korea ( 26 ). Based on Soper's calculation ( 27 ), a minimum sample size of 173 was needed with effect size 0.3, power = 0.8, latent variables = 5, observed variables = 16, and probability level = 0.05.…”
Section: Methodsmentioning
confidence: 99%